2007
DOI: 10.1097/bpb.0b013e32826d1d9b
|View full text |Cite
|
Sign up to set email alerts
|

Superior mesenteric artery syndrome after scoliosis repair surgery: a case study and reassessment of the syndrome's pathogenesis

Abstract: We carried out a retrospective analysis to investigate the prevalence of superior mesentery artery syndrome (SMAS) in children who underwent scoliosis surgical repair at our hospital between 1998 and 2006 and to reassess the syndrome's pathogenesis. Among 133 consecutive pediatric patients, two cases were identified, both 13-year-old girls with idiopathic scoliosis, undergoing surgery using third-generation instrumentation systems. Conservative management achieved resolution of the symptoms without recurrence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 15 publications
0
20
0
2
Order By: Relevance
“…Short-term follow-up (after discharge from hospital) revealed two IS children who developed superior mesenteric artery syndrome (SMAS), several days following discharge from hospital. Both children were re-hospitalized and the symptoms resolved with conservative treatment within two to three weeks [11] . Intermediate-term follow-up revealed one IS child who developed deep vein thrombosis in the inferior vena cava, external iliac and femoral veins one month following discharge.…”
Section: Postoperative Course Parameters -Comparison Between Cp and Imentioning
confidence: 99%
“…Short-term follow-up (after discharge from hospital) revealed two IS children who developed superior mesenteric artery syndrome (SMAS), several days following discharge from hospital. Both children were re-hospitalized and the symptoms resolved with conservative treatment within two to three weeks [11] . Intermediate-term follow-up revealed one IS child who developed deep vein thrombosis in the inferior vena cava, external iliac and femoral veins one month following discharge.…”
Section: Postoperative Course Parameters -Comparison Between Cp and Imentioning
confidence: 99%
“…All of the patients except one were treated conservatively [4, 6, 1619]. In the current study, our patient underwent duodenojejunostomy due to the ineffectiveness of conservative treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Approximately 15 causes of SMAS have been identified, including the following: a narrow SMA-aorta distance or a narrow aortomesenteric vascular angle; high fixation of the duodenojejunal flexure to the ligament of Treitz; a relatively low SMA origin; excessive weight loss (or other secondary causes of mesenteric and retroperitoneal lipid tissue loss, such as burns, anorexia, or cancer); severe injuries, such as head trauma; surgical complications; abnormal peritoneal attachments associated with duodenal malrotation; excessive lumbar lordosis; visceroptosis; and a loose abdominal wall [35]. Additionally, there are case reports in the literature concerning SMAS as a complication of scoliosis surgery [4, 6, 1619]. Zhu and Qiu [4] associated this condition with a contraction of the angle between the SMA and the aorta, resulting from an extension of the SMA trunk that occurs after correction of the vertebral axis in scoliosis surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been comprehensive surgeon-reported complication rates [1]; descriptions of particular complications, such as infections [11], superior mesenteric artery syndrome [4,13], etc; complications related to a certain technique, such as thoracoscopic treatment [8,10]; or complications compared between different techniques, such as hooks versus screws [5,6,12]. Our aim was to define a radiographic system of * P values were calculated using an overall chi square test for all treatment groups for existence of a serious radiographic adverse event (p = 0.427) or a radiographic adverse event (p = 0.88); no significant difference was found between the different surgical treatments; OASF = open anterior instrumented spinal fusion; TASF = thoracoscopic anterior instrumented spinal fusion; PSFH = posterior instrumented spinal fusion with an anchor system that utilized hooks or hooks, wires, and screws (hybrid systems); PSFS = posterior instrumented spinal fusion with an anchor system that utilized a majority of pedicle screws.…”
Section: Discussionmentioning
confidence: 99%